Les substances radioactives dans les objets patrimoniaux - Marion Daval (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Odourless, noiseless and without any specifically perceptible physical form, the presence of radioactive substances in patrimonial objects is not easily detectable. Therefore, the management of this particular patrimony appears problematic, on its practical as well as legal aspects. The fear of their noxiousness and the lack of knowledge about management solutions often leads to the exclusion of these objects, although they are highly emblematic of the 20th century. For a better comprehension of this patrimony, this study is articulated around three main themes: the identification of radioactive objects, the estimation of the hazard and the management of these collections using preventive or curative actions.